Development and implementation of the ECHO model in a school setting to address youth electronic cigarette use in Kansas: A protocol - Leavens, Eleanor L. S.; Roberts, Jordan; Faseru, Babalola; Thompson, Mark; Denes-Collar, Karin; Shah, Hina (Frontiers in Public Health, 2023)
Introduction Schools remain at the frontlines of addressing issues, such as e-cigarette use, that impact students. Despite e-cigarette use remaining a significant public health concern in the U.S., schools have limited resources (e.g., staff, capacity, programming) to address it, especially in rural and frontier areas. This ECHO Pilot Project aimed to build capacity and equip schools and school staff in the state of Kansas to address high rates of youth e-cigarette use by providing prevention support and information on best practices for e-cigarette cessation. Methods and analysis The pilot used the established Project ECHO model to disseminate evidence-based strategies for e-cigarette prevention and cessation among youth to schools across Kansas. The pilot selected 20 interdisciplinary school teams representing both rural and urban middle and high schools across the state to participate in seven ECHO sessions. ECHO sessions proceeded throughout Fall 2021, with the final session in Spring 2022. School participants completed pre-post surveys as well as component-specific surveys following each ECHO session. In addition, each school team created an individualized action plan to comprehensively address e-cigarette use at their school based on the information provided throughout the ECHO. Survey data, school tobacco/nicotine policies, and action plans will be analyzed to assess process and final outcomes. Discussion If successful, this pilot will demonstrate that the ECHO model is an effective platform for building school staff knowledge and skills to implement evidence-based strategies in both urban and rural settings. It is anticipated that the pilot will build capacity and equip schools and school staff to address high rates of youth e-cigarette use by providing support for school-based prevention programs and referrals for e-cigarette cessation which will lessen the burden of nicotine-related problems in Kansas schools and communities. Finally, the pilot will provide evidence that the ECHO model can be successfully and equitably applied in a school setting and may be a viable method for addressing other public health-related issues faced by schools.